Silicon-carbon composite material, preparation method thereof, pole piece, application and electrochemical device

By growing a graphene carbon layer on porous carbon and performing multi-layer carbon coating, a silicon-carbon composite material with excellent electrochemical properties was prepared, which solved the volume expansion and side reaction problems of the silicon-based negative electrode material, and achieved higher cycling performance and rate performance.

CN119650656APending Publication Date: 2025-03-18NINGBO SHANSHAN SILICON-BASED MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411884822.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have poor circulation performance, first-time Coulomb efficiency and rate performance due to volume expansion and side reactions, which hinder their commercial application.

Method used

Using a multi-step preparation method, firstly, the graphene carbon layer is grown in situ on the porous carbon, and silane is deposited on the surface to form the first silicon carbon material. Then, by coating carbon in the first gas phase and the second liquid phase, a dense and macroporous carbon layer structure is formed to enhance the electrical conductivity and mechanical properties of the material.

Benefits of technology

The cycle performance, first-time Coulomb efficiency and rate performance of silicon-carbon composite assembled batteries have been significantly improved, the problems of volume expansion and side reactions have been solved, and the commercialization potential of the materials has been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650656A_ABST
    Figure CN119650656A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material, a preparation method thereof, a pole piece, application and an electrochemical device. The preparation method of the silicon-carbon composite material comprises the following steps: S1, carrying out graphene carbon coating and silane deposition on porous carbon to obtain a first silicon-carbon material; a carbon source system used during graphene carbon coating comprises methane, hydrogen and inert gas; s2, performing first gas-phase carbon coating and second liquid-phase carbon coating on the first silicon-carbon material to obtain a silicon-carbon composite material; and a pore-forming agent is also added when the second liquid phase is coated. The battery assembled by the silicon-carbon composite material disclosed by the invention has better electrochemical performance, and particularly has better cycle performance, first coulombic efficiency and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method, a pole piece, an application and an electrochemical device thereof. Background Art

[0002] Silicon-based materials have the advantages of high specific capacity, abundant natural resources, high safety, and environmental friendliness, and are the mainstream negative electrode materials for the next generation of lithium-ion batteries. However, the volume expansion of silicon-based negative electrodes and side reactions with electrolytes lead to the loss of active lithium and the reduction of Coulombic efficiency (CE), which hinders the commercial application of silicon-based negative electrodes. Therefore, slowing down the expansion of silicon-based materials and reducing the production of side reactions make the commercialization of silicon-based materials possible. Summary of the invention

[0003] The technical problem to be solved by the present invention is to overcome the defects of the prior art that the battery assembled with the silicon material has poor cycle performance, poor first coulomb efficiency and poor rate performance due to the volume expansion of silicon and the side reaction with electrolyte, and provide a silicon-carbon composite material and its preparation method, pole piece, application and electrochemical device. The battery assembled with the silicon-carbon composite material of the present invention has better electrochemical performance, especially better cycle performance, first coulomb efficiency and rate performance.

[0004] The present invention adopts the following technical solutions to solve the above technical problems.

[0005] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:

[0006] S1, performing graphene carbon coating and silane deposition on porous carbon to obtain a first silicon-carbon material; the carbon source system used in the graphene carbon coating includes methane, hydrogen and an inert gas;

[0007] S2. Performing a first gas phase carbon coating and a second liquid phase carbon coating on the first silicon-carbon material to obtain a silicon-carbon composite material; a pore-forming agent is also added during the second liquid phase coating.

[0008] In the present invention S1, the D10 of the porous carbon is preferably 0.1-8 μm, such as 5.2 or 5.4 μm. The D50 of the porous carbon is preferably 6-20 μm, such as 8.6, 8.7 or 8.8 μm. The D90 of the porous carbon is preferably 10-30 μm, such as 14.1, 14.3 or 14.5 μm. The specific surface area of ​​the porous carbon may be 200-2000 m 2 / g, such as 1600, 1650, 1680, or 1700m 2 / g. The pore volume of the porous carbon may be 0.1-1.2cm 3 / g, such as 0.6, 0.64, 0.7 or 0.68 cm 3The pore size distribution of the porous carbon may be 2-50 nm, preferably 10-30 nm, such as 25, 22, 20 or 18 nm.

[0009] In the present invention S1, the porous carbon is preferably ordered mesoporous carbon. According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), pores with a diameter between 2 and 50 nanometers are called mesoporous.

[0010] The method for preparing the ordered mesoporous carbon preferably comprises the following steps: carbonizing a mixture of a mixed solution of a pyrolytic carbon precursor and a template, and removing the template to obtain the ordered mesoporous carbon.

[0011] The residual carbon rate of the pyrolytic carbon precursor may be 20%-70%, preferably 25%-65%, for example 30% or 60%. The residual carbon rate of the pyrolytic carbon precursor may be obtained by GB / T268-87 test.

[0012] The type of the pyrolytic carbon precursor preferably includes one or more of phenolic resin, pitch, glucose, citric acid, sucrose, polyethylene glycol, furan resin, coconut shell, polyvinyl alcohol and methyl cellulose, such as phenolic resin, citric acid, coconut shell or glucose.

[0013] The solvent in the mixed solution of the pyrolytic carbon precursor can be a conventional solvent in the art that can dissolve the pyrolytic carbon precursor, preferably one or more of deionized water, methanol, anhydrous ethanol, propanol, isopropanol and acetone, such as deionized water or ethanol. The mass concentration of the ethanol can be 95%.

[0014] The type of the template can be conventional in the art, such as silicon dioxide or mesoporous molecular sieve. The mesoporous molecular sieve is preferably SBA-15.

[0015] The mass ratio of the pyrolytic carbon precursor to the template is preferably 1:(0.5-2), such as 1:1 or 1:1.5.

[0016] The mixture of the mixed solution of the pyrolytic carbon precursor and the template is preferably obtained by mixing the pyrolytic carbon precursor and the solvent, adding the template, ultrasonically dispersing, and drying. The ultrasonic dispersion time may be 20-40 minutes, for example, 30 minutes. The drying operation may be conventional in the art, for example, drying in a blast drying oven. The drying temperature may be 70-90°C, for example, 80°C. The drying time may be 11-13 hours, for example, 12 hours.

[0017] The carbonization treatment is preferably carried out under an inert atmosphere. The inert atmosphere is preferably argon or nitrogen. The temperature of the carbonization treatment is preferably 800-1000° C., such as 900° C. The time of the carbonization treatment is preferably 1-3 hours, such as 2 hours.

[0018] The method for removing the template can be conventional in the art, such as removal by hydrofluoric acid solution. The mass concentration of hydrofluoric acid in the hydrofluoric acid solution can be 5wt%-15wt%, such as 10wt%. The time for removing the template can be 10-40min, such as 30min.

[0019] After removing the template, the method preferably further includes conventional washing and drying steps in the art. The washing preferably includes alcohol washing and / or water washing.

[0020] In S1 of the present invention, the graphene carbon-coated equipment may be conventional equipment with high temperature function in the art, preferably a rotary kiln, a fluidized bed, a box furnace or a rotary heating furnace, such as a rotary kiln.

[0021] In S1 of the present invention, the inert gas is preferably argon or nitrogen.

[0022] In S1 of the present invention, the volume percentage of methane may be 5%-10%, such as 9.38%, 5.45%, 7.69% or 7.14%. The volume percentage of methane represents the percentage of the volume of methane to the total volume of the carbon source system.

[0023] In S1 of the present invention, the volume ratio of the methane, the hydrogen and the inert gas may be (1-4):(2-12):20, for example, 3:9:20, 1.5:6:20, 2.5:10:20, 2:4:20, 1.5:6:20 or 2:6:20.

[0024] In S1 of the present invention, the mass volume ratio of the porous carbon to the methane may be 2.5 kg: (300-600) L, for example, 2.5 kg: 540 L, 2.5 kg: 270 L, 2.5 kg: 450 L or 2.5 kg: 360 L.

[0025] In S1 of the present invention, the temperature of the graphene carbon coating may be 900-1200°C, for example 1000 or 1100°C.

[0026] In S1 of the present invention, the graphene carbon coating time may be 0.1-8 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h or 7 h.

[0027] In S1 of the present invention, the graphene carbon coating and the silane deposition are preferably performed in the same device. After the graphene carbon coating and before the silane deposition, a step of purging the device with an inert gas is preferably performed. The purging time may be 20-40 minutes, for example 30 minutes.

[0028] In S1 of the present invention, the type of silane used for the silane deposition may be conventional in the art, preferably including silane and / or silane halides. The silane preferably includes one or more of monosilane, disilane, trisilane and tetrasilane, such as monosilane. The silane halide preferably includes one or more of chlorosilane, dichlorosilane, trichlorosilane and tetrachlorosilane, such as tetrachlorosilane.

[0029] In S1 of the present invention, the volume percentage of the silane may be 0%-100% but not 0, preferably 5%-50%, such as 20%, 21%, 25%, 28% or 50%. The volume percentage of the silane represents the percentage of the volume of the silane to the total volume of the system when the silane is deposited.

[0030] In S1 of the present invention, the silane deposition preferably further includes a carrier gas, which is preferably one or more of hydrogen, argon, nitrogen, helium and xenon, such as nitrogen.

[0031] In S1 of the present invention, the temperature of the silane deposition may be 300-800°C, preferably 400-650°C, such as 450, 470, 500 or 550°C.

[0032] In S1 of the present invention, the silane deposition time may be 10 min-24 h, preferably 30 min-8 h, such as 60 min, 180 min, 300 min or 360 min.

[0033] In S2 of the present invention, the silane deposition and the first gas phase carbon coating are preferably performed in the same device. After the silane deposition and before the gas phase carbon coating, a step of purging the device with an inert gas is preferably performed. The purging time may be 20-40 minutes, for example 30 minutes.

[0034] In S2 of the present invention, the carbon source used for the first gas-phase carbon coating may be one or more of alkanes, alkenes and alkynes. The alkanes are preferably one or more of methane, ethane and propane. The alkenes are preferably ethylene and / or propylene. The alkynes are preferably acetylene and / or propyne, such as acetylene.

[0035] In S2 of the present invention, the volume percentage of the carbon source used for the first gas-phase carbon coating may be 0-90% but not 0, preferably 5%-50%, such as 20%, 21.4% or 30%. The volume percentage of the carbon source used for the first gas-phase carbon coating represents the percentage of the volume of the carbon source to the total volume of the gas during the first gas-phase carbon coating.

[0036] In S2 of the present invention, the first gas-phase carbon coating preferably further comprises a carrier gas, which is preferably one or more of hydrogen, argon, nitrogen, helium and xenon, such as nitrogen.

[0037] In S2 of the present invention, the temperature of the first gas-phase carbon coating may be 300-1000°C, preferably 400-800°C, for example 450, 500, 550, 600 or 650°C.

[0038] In S2 of the present invention, the time of the first gas-phase carbon coating may be 1 min-24 h, preferably 30 min-8 h, for example 60 min, 120 min, 180 min, 300 min or 360 min.

[0039] In S2 of the present invention, the carbon source used for the second liquid phase carbon coating may be one or more of phenolic resin, asphalt, glucose, citric acid, sucrose, polyethylene glycol, furan resin, coconut shell, polyvinyl alcohol and methyl cellulose, such as sucrose or phenolic resin.

[0040] In S2 of the present invention, the second liquid phase carbon coating generally further comprises a solvent. The solvent may be a conventional solvent in the art that can dissolve the carbon source used in the second liquid phase carbon coating, preferably one or more of deionized water, methanol, anhydrous ethanol, propanol, isopropanol and acetone, such as deionized water, acetone or ethanol.

[0041] In S2 of the present invention, the type of the pore former preferably includes one or more of potassium hydroxide, phosphoric acid, zinc chloride, glycolic acid and nitric acid, such as glycolic acid. The mass ratio of the pore former to the carbon source during the second liquid phase carbon coating can be 1:(0.1-0.5), for example 1:0.2.

[0042] In S2 of the present invention, the second liquid phase carbon coating is preferably performed under an inert atmosphere. The type of the inert atmosphere preferably includes one or more of hydrogen, argon, nitrogen, helium and xenon, such as argon.

[0043] In S2 of the present invention, the temperature of the second liquid phase carbon coating may be 800-1000°C, for example 900°C.

[0044] In S2 of the present invention, the second liquid phase carbon coating time may be 1-5 hours, for example 2 hours.

[0045] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method as described above.

[0046] The present invention also provides a silicon-carbon composite material, which includes porous carbon filled with nano-silicon particles and a shell layer;

[0047] The shell layer includes a graphene carbon layer, a first carbon layer and a second carbon layer in sequence; the graphene carbon layer is radially distributed; the graphene carbon layer is coated on the porous carbon surface filled with nano-silicon particles; nano-silicon particles are distributed in the graphene carbon layer;

[0048] The average pore size of the second carbon layer is greater than 50 nm.

[0049] In the present invention, the mass content of silicon in the silicon-carbon composite material may be 30%-60%, preferably 35%-55%, for example, 52.9%, 49.5%, 47.9%, 46.7%, 46.5%, 45.4%, 45.3%, 43.9%, 43.8%, 39.5% or 39.3%.

[0050] In the present invention, the specific surface area of ​​the silicon-carbon composite material can be 8-25m 2 / g, preferably 8.5-24m 2 / g, for example, 23.6, 18.6, 13.5, 10.8, 10.2, 9.8, 9.7, 9.6, 9.2 or 8.9.

[0051] In the present invention, the thickness of the second carbon layer may be 8-10 nm.

[0052] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.

[0053] In the present invention, preferably, the electrode sheet is a negative electrode sheet.

[0054] The present invention also provides an application of the pole piece as described above in an electrochemical device.

[0055] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0056] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0057] The reagents and raw materials used in the present invention are commercially available.

[0058] The positive and progressive effects of the present invention are:

[0059] (1) The structure of the silicon-carbon composite material is creatively designed in the present invention. First, a graphene carbon layer is grown in situ and radially on the basis of porous carbon, and then silane is deposited. At this time, the graphene carbon layer can improve the conductivity of the material, and the sheet structure of the graphene carbon layer provides expansion space for nano-silicon particles that have not entered the porous carbon. Furthermore, the graphene carbon layer has better mechanical properties, which can improve the rigidity of the silicon-carbon composite material and thus improve the cycle performance of the battery assembled therefrom. Second, a dense first carbon layer and a macroporous second carbon layer are coated on the surface of the graphene carbon layer. The dense first carbon layer plays a passivation role, preventing the nano-silicon particles with high reaction activity from producing side reactions with the outside world. The macroporous second carbon layer, the graphene carbon layer and the porous carbon form a complete conductive network, which greatly improves the diffusion rate of lithium ions in the silicon-carbon composite material, and significantly improves the rate performance of the battery assembled therefrom.

[0060] (2) The preparation method of the silicon-carbon composite material in the present invention is simple and suitable for large-scale production, which is of great significance to the improvement of the existing gas phase method for preparing silicon-carbon composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of the structure of the silicon-carbon composite material prepared in Example; Figure 1 Part a is a schematic diagram of the overall structure of the silicon-carbon composite material. Figure 1 Part b is a schematic cross-sectional view of the silicon-carbon composite material.

[0062] Figure 2 TEM image of the silicon-carbon composite material obtained in Example 1; Figure 2 Part a and part b are TEM images of the silicon-carbon composite material prepared in Example 1 at different scales.

[0063] Figure 3 This is a cycle performance diagram of the silicon-carbon composite material prepared in Example 1 and Comparative Examples 1-2.

[0064] Figure 4 Rate performance diagram of the silicon-carbon composite materials prepared in Examples 1-2 and Comparative Examples 1-3.

[0065] Description of reference numerals:

[0066] Nano silicon particles-1; porous carbon-2; graphene carbon layer-3; first carbon layer-4; second carbon layer-5. DETAILED DESCRIPTION

[0067] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0068] Example 1

[0069] S1. (1) Phenolic resin (residual carbon content: 60%) was dissolved in anhydrous ethanol (95%) to form a mixed solution. SBA-15 was added to the solution and stirred and ultrasonicated for 30 min. The mass ratio of the two was phenolic resin: SBA-15 = 1:0.5. After stirring and ultrasonicating, the mixture was dried in a forced air drying oven at 80 °C for 12 h to obtain a solid precursor. The solid precursor was carbonized in a tube furnace at 900 °C for 2 h under an argon atmosphere. The product was then placed in a 10 wt% HF solution for 30 min to remove the SBA-15 template. After multiple ethanol and water washings and drying, ordered mesoporous carbon (average pore size: 22 nm, D10: 5.2 μm, D50: 8.6 μm, D90: 14.3 μm, specific surface area: 1680 m 2 / g, pore volume: 0.64g / cm 3 ).

[0070] (2) Using 2.5 kg of ordered mesoporous carbon as the substrate, methane, hydrogen and argon were introduced into a rotary kiln for thermal CVD reaction. The reaction temperature was 1000°C, the reaction time was 3 h, the methane flow rate was 3 L / min, the hydrogen flow rate was 9 L / min, and the argon flow rate was 20 L / min (the volume percentage of methane was 9.38%), so that three-dimensional graphene sheets were in situ grown on the outer surface of the ordered mesoporous carbon.

[0071] (3) After the thermal CVD process is completed, stop introducing methane and hydrogen, use inert gas to purge the equipment for 30 minutes, and then introduce nitrogen and silane for deposition at 500°C. The volume concentration of monosilane is 25%, and the reaction time is 300 minutes to obtain the first silicon-carbon material.

[0072] S2. (1) After the reaction is completed, stop introducing silane and nitrogen and use inert gas to purge the equipment for 30 minutes, then introduce acetylene and nitrogen to perform the first gas phase carbon coating at 600°C. The acetylene volume concentration is 21.4% and the reaction time is 120 minutes.

[0073] (2) Finally, sucrose and glycolic acid (mass ratio of 1:0.2) were dissolved in deionized water to form a mixed solution, and the product of step S2 (1) was added to the mixed solution and dried in a forced air drying oven at 80°C for 12 h, followed by a second liquid phase carbon coating at 900°C in an argon atmosphere for 2 h. The outer coating layer finally formed was a macroporous (average pore size greater than 50 nm) carbon coating layer.

[0074] Example 2

[0075] S1. (1) Dissolve citric acid in anhydrous ethanol (95%) to form a mixed solution, add SBA-15 to the solution and stir and ultrasonicate for 30 min. The mass ratio of the two is citric acid: SBA-15 = 1:1. After stirring and ultrasonicate treatment, place the solution in a forced air drying oven at 80 °C for 12 h to obtain a solid precursor. Place the solid precursor in a tube furnace and carbonize it at 900 °C for 2 h under an argon atmosphere. Then place the product in a 10 wt% HF solution for 30 min to remove the SBA-15 template. After multiple ethanol and water rinses and drying, ordered mesoporous carbon (average pore size: 20 nm, D10: 5.4 μm, D50: 8.6 μm, D90: 14.5 μm, specific surface area: 1700 m 2 / g, pore volume: 0.68g / cm 3 ).

[0076] (2) Using 2.5 kg of ordered mesoporous carbon as the substrate, methane, hydrogen and argon were introduced into a rotary kiln for thermal CVD reaction. The reaction temperature was 1000°C, the reaction time was 3 h, the methane flow rate was 1.5 L / min, the hydrogen flow rate was 6 L / min, and the argon flow rate was 20 L / min (the volume percentage of methane was 5.45%), so that three-dimensional graphene sheets were in situ grown on the outer surface of the ordered mesoporous carbon.

[0077] (3) After the thermal CVD process is completed, stop introducing methane and hydrogen, use inert gas to purge the equipment for 30 minutes, and then introduce nitrogen and silane for deposition at 550°C. The volume concentration of monosilane is 28%, and the reaction time is 300 minutes to obtain the first silicon-carbon material.

[0078] S2. (1) After the reaction is completed, stop introducing silane and nitrogen and use inert gas to purge the equipment for 30 minutes, then introduce acetylene and nitrogen to perform the first gas phase carbon coating at 600°C. The acetylene volume concentration is 21.4% and the reaction time is 120 minutes.

[0079] (2) Finally, phenolic resin and glycolic acid (the mass ratio of the two is 1:0.2) are dissolved in acetone to form a mixed solution, and the product of step 3 is added to the mixed solution and dried in a forced air drying oven at 80°C for 12 hours, and then a second liquid phase carbon coating is performed at 900°C in an argon atmosphere for 2 hours. The final outer coating layer is a macroporous (average pore size greater than 50 nm) carbon coating layer.

[0080] Example 3

[0081] S1. (1) Coconut shell (residual carbon content is 30%) was placed in a tube furnace for heat treatment at 500°C in an argon atmosphere for 3 h to obtain a coconut shell carbon precursor. The coconut shell carbon precursor was crushed and sieved and then dissolved in anhydrous ethanol (95%) to form a mixed solution. SBA-15 was added to the solution and stirred and ultrasonicated for 30 min. The mass ratio of the two was coconut shell carbon precursor: SBA-15 = 1:1.5. After stirring and ultrasonic treatment, the mixture was placed in a forced air drying oven and dried at 80°C for 12 h to obtain a solid precursor. The solid precursor was placed in a tube furnace for carbonization treatment at 900°C in an argon atmosphere for 2 h. The product was then placed in a 15wt% HF solution for reaction for 30 min to remove the SBA-15 template. After multiple ethanol and water washings and drying, ordered mesoporous carbon (average pore size: 18 nm, D10: 5.4 μm, D50: 8.7 μm, D90: 14.3 μm, specific surface area: 1650 m 2 / g, pore volume: 0.7g / cm 3 ).

[0082] (2) Using 2.5 kg of ordered mesoporous carbon as the substrate, methane, hydrogen and argon were introduced into a rotary kiln for thermal CVD reaction. The reaction temperature was 1000°C, the reaction time was 3 h, the methane flow rate was 2.5 L / min, the hydrogen flow rate was 10 L / min, and the argon flow rate was 20 L / min (the volume percentage of methane was 7.69%), so that three-dimensional graphene sheets were in situ grown on the outer surface of the ordered mesoporous carbon.

[0083] (3) After the thermal CVD process is completed, the introduction of methane and hydrogen is stopped, and the equipment is purged with an inert gas for 30 minutes. Then, silane and nitrogen are introduced for deposition at 450°C. The volume concentration of silane is 21%, and the reaction time is 360 minutes to obtain the first silicon-carbon material.

[0084] S2. (1) After the reaction is completed, stop introducing silane and nitrogen and use inert gas to purge the equipment for 30 minutes, then introduce acetylene and nitrogen to perform the first gas phase carbon coating at 600°C. The acetylene volume concentration is 21.4% and the reaction time is 120 minutes.

[0085] (2) Finally, sucrose and glycolic acid (the mass ratio of the two is 1:0.3) are dissolved in anhydrous ethanol to form a mixed solution, and the product of step 3 is added to the mixed solution and dried in a forced air drying oven at 80°C for 12 hours, and then a second liquid phase carbon coating is performed at 900°C in an argon atmosphere for 2 hours. The final outer coating layer is a macroporous (average pore size greater than 50 nm) carbon coating layer.

[0086] Example 4

[0087] S1. (1) Glucose was dissolved in deionized water to form a mixed solution. SBA-15 was added to the solution and stirred for 30 min. The mass ratio of the two was glucose: SBA-15 = 1:2. After stirring and ultrasonic treatment, the mixture was dried in a forced air drying oven at 80 °C for 12 h to obtain a solid precursor. The solid precursor was carbonized in a tube furnace at 900 °C for 2 h under an argon atmosphere. The product was then placed in a 15 wt% HF solution for 30 min to remove the SBA-15 template. After multiple ethanol and water washings and drying, ordered mesoporous carbon (average pore size: 25 nm, D10: 5.4 μm, D50: 8.8 μm, D90: 14.1 μm, specific surface area: 1600 m 2 / g, pore volume: 0.6g / cm 3 ).

[0088] (2) Using 2.5 kg of ordered mesoporous carbon as the substrate, methane, hydrogen and argon were introduced into a rotary kiln for thermal CVD reaction. The reaction temperature was 1200°C, the reaction time was 3 h, the methane flow rate was 2 L / min, the hydrogen flow rate was 4 L / min, and the argon flow rate was 20 L / min (the volume percentage of methane was 7.69%), so that three-dimensional graphene sheets were in situ grown on the outer surface of the ordered mesoporous carbon.

[0089] (3) After the thermal CVD process is completed, the introduction of methane and hydrogen is stopped, and the equipment is purged with an inert gas for 30 minutes. Then, silane and nitrogen are introduced for deposition at 470°C. The volume concentration of monosilane is 21%, and the reaction time is 360 minutes to obtain the first silicon-carbon material.

[0090] S2. (1) After the reaction is completed, stop introducing silane and nitrogen and use inert gas to purge the equipment for 30 minutes, then introduce acetylene and nitrogen to perform the first gas phase carbon coating at 600°C. The acetylene volume concentration is 21.4% and the reaction time is 120 minutes.

[0091] (2) Finally, phenolic resin and glycolic acid (the mass ratio of the two is 1:0.2) are dissolved in acetone to form a mixed solution, and the product of step 3 is added to the mixed solution and dried in a forced air drying oven at 80°C for 12 hours, and then a second liquid phase carbon coating is performed at 900°C in an argon atmosphere for 2 hours. The final outer coating layer is a macroporous (average pore size greater than 50 nm) carbon coating layer.

[0092] Example 5

[0093] The difference from Example 1 is that: Step S1 (2): the methane flow rate is controlled to be 1.5 L / min and the hydrogen flow rate is controlled to be 6 L / min (the volume percentage of methane is 4.45%).

[0094] Example 6

[0095] The difference from Example 1 is that: Step S1 (3): controlling the volume concentration of silane to 28%.

[0096] Example 7

[0097] The difference from Example 2 is that: Step S1 (2): the methane flow rate is controlled to be 3 L / min and the hydrogen flow rate is controlled to be 9 L / min (the volume percentage of methane is 9.38%).

[0098] Example 8

[0099] The difference from Example 3 is that: Step S1 (3): the volume concentration of silane is controlled to be 28%, the reaction time is 300 min, and the temperature is 520°C.

[0100] Example 9

[0101] The difference from Example 4 is that: Step S1 (2): control the methane flow rate to 2 L / min and the hydrogen flow rate to 6 L / min (the volume percentage of methane is 7.14%).

[0102] Example 10

[0103] The difference from Example 1 is that the raw material is commercially available porous carbon (D10: 5.2 μm D50: 8.6 μm D90: 14.4 μm specific surface area: 1740 m 2 / g pore volume: 0.7g / cm 3 , average pore size: 2.5 nm), and step S1 (1) is not performed.

[0104] Comparative Example 1

[0105] The difference from Example 1 is that step S1 (2) is not performed.

[0106] Comparative Example 2

[0107] The difference from Example 1 is that step S2 (2) is not performed.

[0108] Comparative Example 3

[0109] The difference from Example 1 is that the carbon coating method in step S2 (2) is replaced by vapor deposition, the carbon precursor is acetylene, the deposition temperature is 600° C., the deposition time is 360 min, and the volume concentration of acetylene is 21.4%.

[0110] Comparative Example 4

[0111] The difference from Example 1 is that the raw material is commercially available porous carbon, and step S1 (1) is performed, but step S1 (2) is not performed.

[0112] Effect Example 1

[0113] Figure 1 Schematic diagram of the structure of the silicon-carbon composite material prepared in the embodiment. Figure 1 Part a is a schematic diagram of the overall structure of the silicon-carbon composite material. Figure 1 Part b of FIG. 1 is a cross-sectional schematic diagram of the silicon-carbon composite material. Figure 1 It can be seen that the silicon-carbon composite material includes a porous carbon 2 filled with nano-silicon particles 1 and a shell layer; the shell layer includes a graphene carbon layer 3, a first carbon layer 4 and a second carbon layer 5 in sequence; the graphene carbon layer 1 is radially distributed; the graphene carbon layer 3 is coated on the surface of the porous carbon 3 filled with nano-silicon particles 1; nano-silicon particles 1 are distributed in the graphene carbon layer 3; the thickness of the second carbon layer 4 is 8-10nm.

[0114] The silicon-carbon composite material obtained in Example 1 was observed by TEM. Figure 2 shown. Figure 2 Part a and part b of are TEM images of the silicon-carbon composite material prepared in Example 1 at different scales. Figure 2 It can be seen that the graphene carbon layer in the silicon-carbon composite material prepared in Example 1 grows radially and nano-silicon particles are deposited inside.

[0115] The silicon content in the silicon-carbon composite materials obtained in the above embodiments and comparative examples was tested. The testing method is as follows: According to the national standard GB / T38823-2020, the silicon-carbon composite materials obtained in the above embodiments and comparative examples were burned in an oxygen atmosphere using a muffle furnace to react Si in the silicon-carbon composite materials into SiO 2 , carbon burns to CO 2 Discharge and weigh to calculate the mass content of silicon in the silicon-carbon composite material.

[0116] The specific surface areas of the silicon-carbon composite materials obtained in the above examples and comparative examples were measured using a specific surface area and pore size analyzer.

[0117] The test results are shown in Table 1 below.

[0118] Table 1

[0119]

[0120] Effect Example 2

[0121] The silicon-carbon composite material obtained in the above embodiment and comparative example, the conductive agent, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) were respectively prepared into a uniform electrode slurry at a mass percentage of 90:10:5:5, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet; then a lithium sheet was used as a negative electrode and 1 mol / L LiPF 6 / Ethylene carbonate (EC) + dimethyl carbonate (DMC) + ethyl methyl carbonate (EMC) (v / v=1:1:1) electrolyte, Celgard2400 diaphragm, and shell are assembled using conventional production processes. The charge and discharge test is carried out on the LAND battery test system of Wuhan Landian Electronics Co., Ltd. at room temperature, 0.2C constant current charge and discharge, and the charge and discharge voltage is limited to 0.005-3V.

[0122] The test results are shown in Table 2 and Figure 3 shown.

[0123] Table 2

[0124]

[0125] Figure 3 The figure is a cycle performance diagram of the silicon-carbon composite material obtained in Example 1 and Comparative Examples 1-2. Figure 3 It can be seen that compared with Comparative Examples 1-2, the battery assembled with the silicon-carbon composite material prepared in Example 1 has significantly better cycle performance.

[0126] The current density of the rate performance test is 0.1C, 0.2C, 0.5C, 1C, 2C, and 0.1C. The test results are shown in Table 3 and Figure 4 shown.

[0127] Table 3

[0128]

[0129] Combined with the above Tables 1 to 3: It can be seen from the comparison of Examples 1-10 with Comparative Examples 1-4 that the present application achieves different performances of the prepared silicon-carbon composite materials by regulating the preparation process of different ordered mesoporous carbons, the graphene carbon coating process, the first gas phase carbon coating and the second liquid phase carbon coating process parameters during the preparation process.

[0130] in,

[0131] Comparing Example 1 with Example 5, it can be concluded that: 4 Too low an input amount and concentration will result in incomplete growth of 3D graphene sheets and limited distribution space, which will significantly reduce the initial effect of the silicon-carbon composite material.

[0132] By comparing Example 1 with Example 6, it can be concluded that the more silane gas is introduced, the more active silicon particles are attached to the porous carbon and 3D graphene sheets. However, since the higher the concentration of silane, the faster the decomposition rate, the degree of silicon particles deposited on the surface is higher than that deposited in the pores. Therefore, the silicon-carbon composite material prepared in Example 6 has relatively low first efficiency, capacity retention rate and rate performance.

[0133] Comparing Example 3 with Example 8, it can be concluded that SiH 4 The amount and concentration of the input and the reaction temperature are high, SiH 4 The higher the conversion rate into silicon particles, the higher the capacity and the higher the silane utilization rate of the silicon-carbon negative electrode material.

[0134] Compared with Example 1, in Comparative Example 1, step S1 (2) is not performed, so that part of the silicon particles are deposited on the outer surface of the carbon substrate. Since there is no expansion space for these silicon particles, they break in the subsequent cycles, which increases the expansion rate of the negative electrode material and has a lower capacity retention rate. Due to the lack of the promotion effect of the 3D graphene sheet layer, the Li + The transmission capacity is not ideal. Figure 3 , 4 As shown, the battery assembled with the silicon-carbon composite material prepared in Comparative Example 1 is inferior to that of Example 1 in terms of cycle and rate performance.

[0135] Compared with Example 1, Comparative Example 2 does not perform step S2 (4), so that the outermost layer of the silicon-carbon composite material has no carbon coating layer, so that the overall specific surface area of ​​the silicon-carbon composite material is increased, and the holes, 3D graphene sheets and active silicon particles that are not coated with carbon will directly contact the electrolyte, thereby significantly reducing the initial effect of the silicon-carbon composite material. At the same time, the silicon particles continue to contact with the electrolyte in the subsequent process to produce a continuous volume effect, such as Figure 3 As shown, it directly affects the capacity retention rate of the silicon-carbon composite material.

[0136] Compared with Example 1, the carbon coating method in step (4) of Comparative Example 3 is replaced by vapor deposition. After treatment, the specific surface area of ​​the silicon-carbon composite material is effectively reduced, and the initial efficiency is improved. However, due to the vapor coating, the outer carbon layer presents a lamellar coating, and it is impossible to form a macroporous directional channel to promote Li + transmission, so that the rate performance is maintained at a low level; such as Figure 4 As shown, the rate performance of the battery assembled with the silicon-carbon composite material prepared in Comparative Example 3 is inferior to that of Example 1 and Example 2.

[0137] Therefore, compared with common silicon-carbon composite materials, the batteries assembled with silicon-carbon composite materials prepared in various embodiments of the present invention have excellent cycle performance and rate performance. The performance improvement in this invention is mainly attributed to the overall design of the silicon-carbon composite material structure. Moreover, the preparation method of the silicon-carbon composite material in the present invention is simple and suitable for large-scale production, which is of great significance to the improvement of the performance of existing gas phase silicon-carbon.

[0138] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1, performing graphene carbon coating and silane deposition on porous carbon to obtain a first silicon-carbon material; the carbon source system used in the graphene carbon coating includes methane, hydrogen and an inert gas; S2. Performing a first gas phase carbon coating and a second liquid phase carbon coating on the first silicon-carbon material to obtain a silicon-carbon composite material; a pore-forming agent is also added during the second liquid phase coating.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1) to (7): (1) The D10 of the porous carbon is 0.1-8 μm, for example 5.2 or 5.4 μm; (2) The D50 of the porous carbon is 6-20 μm, for example 8.6, 8.7 or 8.8 μm; (3) The D90 of the porous carbon is 10-30 μm, for example, 14.1, 14.3 or 14.5 μm; (4) The specific surface area of ​​the porous carbon is 200-2000m 2 / g, such as 1600, 1650, 1680, or 1700m 2 / g; (5) The pore volume of the porous carbon is 0.1-1.2 cm 3 / g, such as 0.6, 0.64, 0.7 or 0.68 cm 3 / g; (6) The pore size distribution of the porous carbon is 2-50 nm, preferably 10-30 nm, such as 25, 22, 20 or 18 nm; (7) The porous carbon is ordered mesoporous carbon; The method for preparing the ordered mesoporous carbon preferably comprises the following steps: carbonizing a mixture of a mixed solution of a pyrolytic carbon precursor and a template agent, and removing the template agent to obtain the ordered mesoporous carbon; The residual carbon rate of the pyrolytic carbon precursor is preferably 20%-70%, more preferably 25%-65%, for example 30% or 60%; the type of the pyrolytic carbon precursor preferably includes one or more of phenolic resin, asphalt, glucose, citric acid, sucrose, polyethylene glycol, furan resin, coconut shell, polyvinyl alcohol and methyl cellulose, such as phenolic resin, citric acid, coconut shell or glucose; the mass ratio of the pyrolytic carbon precursor to the template is preferably 1: (0.5-2), for example 1: 1 or 1: 1.5; the temperature of the carbonization treatment is preferably 800-1000 ° C, for example 900 ° C; the time of the carbonization treatment is preferably 1-3h, for example 2h.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1)-(10): (1) In S1, the inert gas is argon or nitrogen; (2) In S1, the volume percentage of methane is 5%-10%, for example, 9.38%, 5.45%, 7.69% or 7.14%; the volume percentage of methane represents the percentage of the volume of methane to the total volume of the carbon source system; (3) In S1, the volume ratio of the methane, the hydrogen and the inert gas is (1-4):(2-12):20, for example, 3:9:20, 1.5:6:20, 2.5:10:20, 2:4:20, 1.5:6:20 or 2:6:20; (4) In S1, the mass volume ratio of the porous carbon to the methane is 2.5 kg: (300-600) L, for example, 2.5 kg: 540 L, 2.5 kg: 270 L, 2.5 kg: 450 L or 2.5 kg: 360 L; (5) In S1, the temperature of the graphene carbon coating is 900-1200°C, for example, 1000 or 1100°C; (6) In S1, the graphene carbon coating time is 0.1-8 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or 7 hours; (7) In S1, the type of silane used in the silane deposition includes silane and / or silane halide; the type of silane preferably includes one or more of monosilane, disilane, trisilane and tetrasilane, such as monosilane; the type of silane halide preferably includes one or more of chlorosilane, dichlorosilane, trichlorosilane and tetrachlorosilane, such as tetrachlorosilane; (8) In S1, the volume percentage of the silane is 0%-100% but not 0, preferably 5%-50%, such as 20%, 21%, 25%, 28% or 50%; the volume percentage of the silane represents the percentage of the volume of the silane to the total volume of the system during silane deposition; (9) In S1, the temperature of the silane deposition is 300-800°C, preferably 400-650°C, for example 450, 470, 500 or 550°C; (10) In S1, the silane deposition time is 10 min-24 h, preferably 30 min-8 h, for example 60 min, 180 min, 300 min or 360 min.

4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1) to (9): (1) In S2, the carbon source used for the first gas-phase carbon coating is one or more of alkanes, alkenes and alkynes; the alkanes are preferably one or more of methane, ethane and propane; the alkenes are preferably ethylene and / or propylene; the alkynes are preferably acetylene and / or propyne, such as acetylene; (2) In S2, the volume percentage of the carbon source used for the first gas-phase carbon coating is 0-90% but not 0, preferably 5%-50%, such as 20%, 21.4% or 30%; the volume percentage of the carbon source used for the first gas-phase carbon coating represents the percentage of the volume of the carbon source to the total volume of the gas during the first gas-phase carbon coating; (3) In S2, the temperature of the first gas-phase carbon coating is 300-1000°C, preferably 400-800°C, for example 450, 500, 550, 600 or 650°C; (4) In S2, the first gas-phase carbon coating time is 1 min-24 h, preferably 30 min-8 h, for example 60 min, 120 min, 180 min, 300 min or 360 min; (5) In S2, the carbon source used in the second liquid phase carbon coating is one or more of phenolic resin, asphalt, glucose, citric acid, sucrose, polyethylene glycol, furan resin, coconut shell, polyvinyl alcohol and methyl cellulose, such as sucrose or phenolic resin; (6) In S2, the type of the pore former includes one or more of potassium hydroxide, phosphoric acid, zinc chloride, glycolic acid and nitric acid, such as glycolic acid; (7) In S2, the mass ratio of the pore former to the carbon source during the second liquid phase carbon coating is 1:(0.1-0.5), for example, 1:0.2; (8) In S2, the temperature of the second liquid phase carbon coating is 800-1000°C, for example, 900°C; (9) In S2, the second liquid phase carbon coating time is 1-5 hours, for example, 2 hours.

5. A silicon-carbon composite material, characterized in that: The invention discloses a novel nanostructured carbon foam. The nanostructured carbon foam is prepared by the preparation method described in any one of claims 1 to 4.

6. A silicon-carbon composite material, characterized in that: It includes porous carbon filled with nano-silicon particles and a shell layer; The shell layer includes a graphene carbon layer, a first carbon layer and a second carbon layer in sequence; the graphene carbon layer is radially distributed; the graphene carbon layer is coated on the porous carbon surface filled with nano-silicon particles; nano-silicon particles are distributed in the graphene carbon layer; The average pore size of the second carbon layer is greater than 50 nm.

7. The silicon-carbon composite material according to claim 6, characterized in that: The silicon-carbon composite material satisfies one or more of the following conditions (1)-(3): (1) In the silicon-carbon composite material, the mass content of silicon is 30%-60%, preferably 35%-55%, for example, 52.9%, 49.5%, 47.9%, 46.7%, 46.5%, 45.4%, 45.3%, 43.9%, 43.8%, 39.5% or 39.3%; (2) The specific surface area of ​​the silicon-carbon composite material is 8-25m 2 / g, preferably 8.5-24m 2 / g, for example, 23.6, 18.6, 13.5, 10.8, 10.2, 9.8, 9.7, 9.6, 9.2 or 8.9; (3) The thickness of the second carbon layer is 8-10 nm.

8. A pole piece, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 5-7.

9. Use of the electrode piece according to claim 8 in an electrochemical device.

10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 8.

Citation Information

Cited By

  • Preparation method of multi-stage ordered silicon-carbon negative electrode material

    CN120117591A